(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2015)
Cardiac tamponade (CT) is a clinical emergency, characterised by pressure on the heart due to accumulation of fluid in the pericardial space, which may be blood, pus or other fluids. CT impairs ventricular filling during diastole and thus reduces cardiac output. It is an important cause of sudden natural death due to cardiovascular involvement. Cardiovascular causes account for more than 45–50% cases of sudden deaths. Among the various causes of CT, rupture of acute myocardial infarction (RAMI) and rupture of dissecting ascending aortic aneurysm (RD3A) are most common. There is very scarce data in literature on the incidence of CT as a cause of death in the cases of sudden deaths, except one large study and most other case reports. Death due to CT remains unobserved in almost 50% of cases and even if observed, CT due to haemopericardium (HP) in cases of RAMI gives little time to clinician to make a correct diagnosis and treatment, leading to suspicion about cause and manner of death and many legal complications. Thus, the present study was undertaken to find out the incidence of CT in the cases of sudden death, the frequency of various causes of CT, age groups affected, its pathology and survival time. This study was conducted in the Department of Forensic Medicine & Toxicology at Indira Gandhi Medical College, Nagpur. During a period of two years, 2,759 medico-legal autopsies were performed in this department, of which in 189 cases there was sudden natural death, which were selected for the present study, of which 9 patients died due to CT. All the nine patients of CT were male. CT is the third most common cause of death due to myocardial infarction (MI) after only to rhythm disturbances and cardiogenic shock. It is most often related to HP, attributable to either RAMI or intra-pericardial RD3A, though in our study it was only RAMI.